True evil - Iles, Greg. (London : Hodder, 2006)
Dr Chris Shepard is shocked when Special Agent Alexandra Morse informs Chris that his wife is plotting to kill him, and asks for his help in stopping Andrew Rusk, a man who has made his living by killing people's spouses.
Keywords: Mystery fiction; Suspense fiction; United States. Federal Bureau of Investigation -- Fiction